Sudden cardiac death in athletes - a brief overview - Tucker, R. (The Science of Sport, 2018)
udden cardiac death is the subject of my latest #fourminutemull, and it`s a lousy, horrible, no-good topic. It gets discussed, or though about, in the most tragic of circumstances, because it invariably means that a young, athletic person has died participating in sport. Everything else is made trivial by comparison.